Electromagnetic Wave Propagation from Low-Earth Orbit Satellite to Ground Station Considering Interpolated Atmospheric Environments - Kim, Changseong; Na, Dong Yeop; Park, Yong Bae (IEEE Access, 2021)
We propose a novel method to calculate the electromagnetic (EM) wave propagation from low-earth orbit satellite (LEO) to a ground station based on the physical optics (PO), ray tracing technique, and geometric optics (GO) considering interpolated atmospheric environments. Our method includes the reflector antenna analysis using PO, the interpolation of the meteorological data using PCHIP and Kriging interpolation, transmission analysis using ray tracing and geometrical optics. Tropospheric and stratospheric environments are modeled using meteorological data-air pressure and temperature, relative humidity, and rain rate-measured at 9 different radiosonde observatories in and around South Korea. Furthermore, we utilize Piecewise Cubic Hermite Interpolating Polynomial (PCHIP) and Kriging-exponential methods for vertical and horizontal interpolations of the raw meteorological data, respectively. Hence, the interpolated atmospheric environments are amenable to the best use of ray tracing technique and GO. Subsequently, effective refractive indices of the stratified media can be extracted via millimeter-propagation-model93. The simplified Appleton-Hartree equation characterizes the ionospheric environment. Considering a sun-synchronous orbit satellite passing through South Korea, we calculate atmospheric attenuation, boresight error, received power, and compensation angle of satellite antenna for various conditions.
Keywords: Atmospheric attenuation; Atmospheric environment; Effective refractive index; Interpolating polynomials; Kriging interpolation; Low earth orbit satellites; Millimeter propagation; Sun-synchronous orbit satellites; atmospheric environments; Electromagnetic wave propagation; low-earth orbit satellite; piecewise cubic Hermite interpolating polynomial; ray tracing technique